Ductus Arteriosus Stenting as a Method of Palliative Treatment of Truncus Arteriosus Type A3: Literature Review and Clinical Case - Tetyana Ye. Hura; Anzhelika O. Mykhailovska; Oleksandra O. Motrechko; Andrii V. Maksymenko (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. Van Praagh A3 variant of truncus arteriosus (TA A3) is a condition when the one pulmonary artery branch origins from the TA, the other is filled through the patent ductus arteriosus (PDA).PDA constriction in the early neonatal period can cause absence of blood supply to the one pulmonary artery branch. To prevent this, prolonged infusion of prostaglandin E1, PDA stenting or systemic-to-pulmonary shunt are used. These methods allow to postpone total repair (TR) and reduce mortality risks associated with neonatal period.The aim. To analyze research papers dedicated to endovascular approach of TA A3 staged treatment and to present our own experience.Materials and methods. We conducted a systematic literature search and analyzed various options for the TA A3 staged treatment. After the review, we used endovascular approach as the first stage of treatment in our clinical case.We studied a newborn weighing 4 kg with TA A3 (left pulmonary artery branch origins from the non-coronary sinus of the truncal valve, right pulmonary artery branch filling through the PDA). Nakata index was 83 mm2/m2. McGoon ratio was 1. We decided to perform PDA stenting with the aim of postponing surgical correction until the patient’s optimal age and weight.Discussion. In total, the number of publications about TA A3 staged treatment is limited. Most institutions prefer TA A3 staged treatment in newborns, because it is associated with a lower risk of complications than early TR. In our clinical case, the first step was PDA stenting. The staged approach allowed us to perform TR with a good result at the age of 3 months. Before TR, Nakata index and McGoon ratio were increased to 248 mm2/m2 and 1.9, respectively.Conclusions. The current trend of TA A3 repair has few different options of staged treatment. Staged approach helps to get out of the newborn period and achieves the optimal condition for TR. Our patient successfully received PDA stenting as the first stage of treatment, which created conditions for the pulmonary artery branches growth. The second stage was TR with good long-term results. After analyzing the publications, we noted that the use of endovascular PDA stenting is a good and safe alternative to surgical palliative treatment.